Каменный склеп кургана Х Белогорского курганного могильника - Колтухов, С.Г. (Археологія і давня історія України, 2019)
Статья посвящена характеристике погребальной архитектуры основной гробницы кургана Х Белогорского курганного могильника скифской знати, расположенного на куэсте Ак-Кая на границе Горного и Степного Крыма. Курган датируется второй половиной IV в. до н. э. As a result of the excavations completed in 2001 it became clear that the barrow X is one of elite barrows of Scythia. The crypt was constructed by Bosporan masters, whereas the mound of the barrow was built in Scythian traditions. Barrow X differs from the barrow of Besh-Oba IV which is located on the same necropolis but Scythian traditions are much more brightly expressed in it (Koltukhov, Senatorov 2019). The period of construction of this barrow can be dated to the second half of the 4th century BC. Possibly, the barrow IV precedes the barrow X and belongs to the moment when the Crimean Scythia and the clan «dynasty» of it’s nomarchs only began to form and natives of Steppe Scythia became its first representatives. Barrow X was built later, at that time when connections of new local dynasty with Bosporan kingdom got stronger, and the building of tombs in traditions of Bosporan funeral architecture became a norm in a funeral ceremony of privileged class of Crimean Scythia.